الأليكسيثيميا وعلاقتها باتخاذ القرار لدى طلاب الجامعة - مصطفى، فاطمة محمد الزاهر عبدالله (جامعة كفر الشيخ - كلية التربية, 2017)
يهدف هذا البحث إلى التعرف على الأليكسيثيميا وعلاقتها باتخاذ القرار لدى طلاب الجامعة، كذلك التعرف على الفروق بين الذكور والإناث في كل من الإلكسيثيما واتخاذ القرار. تكونت العينة من (١٧٤) طالب وطالبة من كلية التجارة بجامعة عين شمس، تتراوح أعمارهم ما بين (١٩ -٢١) سنة، منهم (٨٩) من الذكور و(٨٥) من الإناث. استخدمت الباحثة الأدوات التالية: مقياس تورنتو للألكسيثيميا ترجمة وتقنين/ علاء الدين كفافي وفؤاد الدواش-، مقياس اتخاذ القرار-إعداد سيف الدين يوسف عبدون-، استمارة المستوى الاجتماعي الاقتصادي للأسرة-إعداد عبد العزيز الشخص-. أسفرت النتائج عن وجود ارتباط سالب دال إحصائياً بين الألكسيثيما والقدرة على اتخاذ القرار، كذلك وجود فروق دالة إحصائيا بين درجات الذكور والإناث في الأليكسيثيميا لصالح الإناث، كما أسفرت النتائج عن وجود فروق دالة إحصائياً بين درجات الذكور والإناث في اتخاذ القرار لصالح الذكور، وأخيراً لم توجد علاقة بين الألكسيثيما والمستوى الاجتماعي الاقتصادي للأسرة.
This research aimed at investigating the relation between alexythemia and decision- making among university students; also investigate the differences between males and females in both alexithymia and decision- making. The sample included 174 students from the Faculty of Commerce at Ain Shams University, ranging from the ages of 19 to 21 years old. 89 students were males and the other 85 students were females. The researcher used the following tools: The Toronto Scale of alexythemia -Translated by Alaa Eldin Kafafi and Fouad Aldawash, the Scale of Decision- making- by Saif Eldin Yousef Abdoon, Socio-Economic Level of the Family Form - by Abdul Aziz Al-Shakhs. The results revealed a statistically significant negative correlation between alexythemia and decision-making ability. More over the results showed a statistically significant differences between males and females in alexythemia and it is more in females than males. The results also revealed a statistically significant differences between males and females in decision-making and it is more in males than females, finally, there was no relation between alexythemia and the socio-economic level of the family.
Keywords: الصحة النفسية -- الرعاية الاجتماعية -- التربية الخاصة -- طلبة الجامعات